A comparative study on the efficacies of gonadotropin-releasing hormone (GnRH) agonist and GnRH antagonist in neoadjuvant androgen deprivation therapy combined with transperineal prostate brachytherapy for localized prostate cancer. Issue 1 (December 2016) - Miki, Kenta; Sasaki, Hiroshi; Kido, Masahito; Takahashi, Hiroyuki; Aoki, Manabu; Egawa, Shin
Abstract Background Neoadjuvant androgen deprivation therapy (ADT) has been suggested to confer several clinical benefits in patients with prostate cancer (PCa) undergoing transperineal prostate brachytherapy (TPPB). Unlike gonadotropin-releasing hormone (GnRH) receptor agonists, a GnRH antagonist such as degarelix can achieve castrate levels of testosterone without testosterone flare. However, normalization of serum testosterone levels following completion of neoadjuvant ADT in either form of treatment has never been compared in clinical trials. Methods/Design This is a single-center, open-label, randomized controlled study that will compare the efficacy and safety of degarelix with those of existing GnRH agonists combined with125 I-TPPB. A total of 56 patients with low/intermediate-risk clinically localized PCa will be enrolled and randomized to one of two treatment groups: the GnRH agonist group and the degarelix group. Patients in the GnRH agonist group will receive leuprorelin acetate or goserelin acetate, and those in the degarelix group will receive the initial dose of 240 mg as 2 subcutaneous injections of 120 mg each, and then 80 mg of maintenance doses every 4 weeks for 12 weeks. Those randomly assigned to the 12-week intervention period will subsequently undergo 48-weeks of follow-up after125 I-TPPB. The primary endpoint is defined as normalization of serum testosterone levels (>50 ng/dL) following completion of neoadjuvant ADT. All patients will be assessed every 4 weeks for the first 24 weeks, then every 12 weeks for the next 36 weeks after administrations of these drugs. Secondary endpoints are the proportion of normalized serum luteinizing hormone (LH) and follicle-stimulating hormone (FSH), the percent reduction in prostate specific antigen (PSA) compared with pretreatment levels, the percent reduction in total prostate volume (TPV) during neoadjuvant ADT, the percent increase in TPV after125 I-TPPB, the percent reduction in hemoglobin, serum alkaline phosphatase (ALP), changes in free testosterone and bone mineral content measurement, the proportion of patients who have serum testosterone levels over 50 ng/dL at 12 weeks following completion of neoadjuvant ADT, and the improvement of quality of life (QOL). Discussion The present study will provide additional insight regarding the benefit and potency of degarelix and will examine its potential as a new option for administration in neoadjuvant ADT. Trial registration Identification number:UMIN000015519 . Registration date: October 24, 2014.